An Analysis of Strategies and Problems in English E-mail Writing of Employees Working on a Thai Commercial Bank in Bangkok, Thailand - Chamnan-asawakul, Thammawat; Sertpunya, Sarinrat; Nakpathumswat, Prasit; Ekwarangkoon, Pikun (Rajamangala University of Technology Tawan-ok Social Science Journal, 2025)
This study utilized a mixed research design, integrating both quantitative and qualitative methods to investigate the challenges of English email writing among bank employees and to explore the strategies they employ to manage these difficulties. For data collection, the study analyzed 172 English emails sent and received by 63 bank employees between May 1, 2023, and July 31, 2023. The purpose was to classify email types and examine writing issues along with strategies for improvement. The data were analyzed using descriptive statistics including frequency, percentage, mean, and standard deviation, along with comparative analysis through t-tests and F-tests. The findings showed that the most frequently received email types were Informational emails (33 items, 19.19%), followed by Request emails (25 items, 14.53%), Updating emails (18 items, 10.47%), Invitation emails (17 items, 9.88%), and Attachment emails (16 items, 9.30%). An analysis of grammar, spelling, and punctuation errors revealed that the most common mistakes occurred in the use of adjectives, verbs, and spelling. No statistically significant difference (α = .05) was found in English email writing styles between male and female employees. However, at the sub-variable level, a significant difference was identified in how employees addressed the challenges of writing emails, especially regarding the clarity of using online resources to enhance writing and make a favorable impression on recipients. This was supported by post hoc analysis using the Least Significant Difference (LSD) method. Both male and female employees, from various experience levels, often used translation tools such as Google Translate, DeepL, Wordvice AI, Alexa Translations, and Bing Microsoft Translator to reduce errors. Employees with less than five years of experience generally reported higher accessibility to these tools than those with over fifteen years of experience.